PENGARUH HARGA DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA PADA DEALER IRAMA MOTOR PONOROGO TAHUN 2013 - Angga hadi saputra (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study aims to determine whether or not the effect of price and service, either simultaneously or partially on purchasing decisions Yamaha motorcycles in Irama Motor Dealer Ponrogo in 2013. The population in this study are all customers who have purchased a Yamaha motorcycle in dealer Irama Motor Ponorog in 2013. The samples in this study using incidental sampling. Hypotheses were tested using multiple linear regression and product moment correlation. The results showed that no significant effect partially between price with purchase decision Yamaha motorcycle in dealer Irama Motor Ponorogo. There is significant influence between services with purchasing decisions Yamaha motorcycle in dealer Irama Motor. Simultaneously there is a significant effect between price and service to the purchase decision Yamaha motorcycle in dealer Irama Motor Ponorogo.